WAYS TO IMPROVE THE PROCESS OF FORMING ACMEOLOGICAL COMPETENCE OF FUTURE EDUCATION MANAGERS IN HIGHER PEDAGOGICAL EDUCATION INSTITUTIONS - Ткачук, Лариса (Modern engineering and innovative technologies, 2023)
The article proposes ways to improve the process of its formation in higher pedagogical education institutions on the basis of determining the state of formation of acmeological competence of future education managers. The reasons for the predominantly lo